Incidência de COVID-19 em pacientes com diagnóstico clínico presuntivo de dengue na região do Triângulo Mineiro, Brasil em um período pré vacinação - Andrade, Camila Moreira (2022)
In 2020 and 2021, the world faced a SARS-CoV-2 pandemic, causing COVID-19, where Brazil ranked first in the world in number of cases and deaths; however, simultaneously, the country has faced Dengue epidemics since 1986, which could cause severe collapse of the public health system. Both infections have similar initial symptoms, which can lead to an incorrect diagnosis. The main objective of the present retrospective cohort study was to investigate the presence of anti-SARS-CoV-2 antibodies in a panel of serum samples from patients with clinical signs and symptoms of dengue virus infection in the Southeast region, Brazil. The period from January/2019 to April/2021 was selected, to observe the kinetics of the pre-pandemic and pandemic periods, prior to the COVID-19 vaccination campaign in the country. A total of 2,969 serum samples from patients residing in the Northern Triangle, State of Minas Gerais, Brazil, were analyzed using the Capture IgM Dengue ELISA and the COVID-19 IgG/ IgM Rapid Test Device. In general, it was observed that, in addition to serum samples with the presumptive diagnosis of dengue, as the pandemic progressed, the numbers of SARS-CoV-2 positive samples were becoming larger than the numbers of Dengue positive samples. Consequently, the number of COVID-19 patients became underestimated, increasing the likelihood of risks to patients with worsening infection status, as well as to public health.